Using big data to make better decisions in the digital economy - Tan, Kim Hua; Ji, Guojun; Lim, Chee Peng; Tseng, Ming-Lang (Taylor & Francis, 2017)
The question this special issue would like to address is how to harvest big data to help decision-makers to deliver better fact-based decisions aimed at improving performance or to create better strategy? This special issue focuses on the big data applications in supporting operations decisions, including advanced research on decision models and tools for the digital economy. Responds to this special issue was great and we have included many high-quality papers. We are pleased to present 13 of the best papers. The techniques presented include data mining, simulation and expert system with applications span across online reviews, food retail chain to e-health.